раскройте скобки 1)b+(-7m+2n) 2)-3p-(-5x+2y) 3)-(a-4b)+(-8x+3y) 4)(a—9)-(13-a)+(11-a) решите уравнение 1)-2x+7x=-10 2)3y+(4y-2)=0 3)-(x+6)+3*(x+2)=0

раскройте скобки 1)b+(-7m+2n) 2)-3p-(-5x+2y) 3)-(a-4b)+(-8x+3y) 4)(a—9)-(13-a)+(11-a) решите уравнение 1)-2x+7x=-10 2)3y+(4y-2)=0 3)-(x+6)+3*(x+2)=0

  • 1) b-7m+2n

    2)-3p+5x-2y

    3)-a+4b-8x+3y

    4)a+9-13+a+11-a=a+7

    1)-2x+7x=-10

    5x=-10

    x=-2

    2)3y+(4y-2)=0

    3y+4y-2=0

    7y=2

    y=2/7

    3)-(x+6)+3*(x+2)=0

    -x-6+3x+6=0

    2x=0

    x=0

    4)2*(y-9)-5*(y-3,6)=27

    2y-18-5y+18=27

    -3y=27

    y=-9

  • 1)b+(-7m+2n)=b-7m+2n

    2)-3p-(-5x+2y) = -3p+5х-2y 3)-(a-4b)+(-8x+3y) =-a+4b -8x+3y 4)(a—9)-(13-a)+(11-a)=a+9-13+a+11-a

    решите уравнение 1)-2x+7x=-10

    5x=-10

    x=-2

    2)3y+(4y-2)=0

    3y+4y-2=0

    7y=2

    y=0,2

    3)-(x+6)+3*(x+2)=0

    -x-6+3x+6=0

    2x=-6+6

    2x=0

    x=0

    4)2*(y-9)-5*(y-3,6)=27

    2y-18-5y+18=27

    2y-5y=27+18-18

    -3y=27

    y=-9